2018
DOI: 10.1039/c8cc06994h
|View full text |Cite
|
Sign up to set email alerts
|

Templated synthesis of spherical RNA nanoparticles with gene silencing activity

Abstract: RNA has inherent therapeutic and structural properties that make it an important component of biologically-functional nanoparticles. Using DNA-amphiphiles as synthetic templates, we report the synthesis of two classes of RNA-amphiphiles that self-assemble into spherical nanoparticles in aqueous solution and show gene silencing activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In order to provide evidence of gene knockdown at the RNA level, we targeted the APOB gene in HepG2 cells. 35 We quantified the relative silencing by measuring mRNA degradation with RT-qPCR. The data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to provide evidence of gene knockdown at the RNA level, we targeted the APOB gene in HepG2 cells. 35 We quantified the relative silencing by measuring mRNA degradation with RT-qPCR. The data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These methods include 1) the separation is proceeded by the differences in molecular weights, such as dialysis, ultrafiltration, and electrophoresis gel, [69] 2) reversed-phase chromatography exerts separation by the polar differences, [70,71] 3) size exclusion chromatography exerts separation by the differences in molecular sizes, [72][73][74][75] and 4) anion exchange chromatography exerts separation by the charge density differences. [76] The most commonly used hydrophobic moieties ( Figure 6A-G) of DNA amphiphiles can be roughly divided into the following categories: 1) lipids (such as fatty chains, cholesterol, and their analogs), [77][78][79][80] 2) -conjugated molecules (including hydrophobic fluorescent dyes and conjugated polymers), [76,81,82] 3) strongly hydrophobic polymers (polystyrene, polynorbornene (PNB) derivatives grafted with aromatic rings), [74,75] 4) biodegradable polymers ((polylactic acid (PLA), polycaprolactone (PCL), and polylactic acid-glycolic acid (PLGA)), [66,[83][84][85][86] 5) stimulus-responsive polymers ((temperature-responsive poly(Nisopropylacrylamide) (PNIMAP), [64] pH-responsive polyacrylic acid (PAA)), [87] 6) some other hydrophobic molecules ((poly phosphorylated hexaethylene (HE n ), [88] polypropylene oxide (PPO)), [89][90][91] and 7) aggregation-induced emission (AIE)-based molecules. [92,93] These hydrophobic moieties are chemically conjugated to DNAs (with different sequence lengths) through covalent bonds, producing various DNA amphiphiles.…”
Section: The Synthesis Of Dna-organic Hybrid Amphiphilesmentioning
confidence: 99%
“…A more recent study from the Sleiman group reported two methods for conjugating specific RNA strands with hydrophobic chains, allowing the formation of RNA-amphiphiles and subsequent efficient gene-silencing capability [ 88 ]. As shown in Fig.…”
Section: Bioanalytical and Biomedical Applications Of Dna–lipid Probesmentioning
confidence: 99%
“…7 A and B, by employing dibenzocyclooctyne group (DBCO)-labeled DNA-amphiphile as a template, azide-modified RNA was directly attached to the hydrophobic chain via ‘click-chemistry’ and the hybridized DNA could then be removed by adding DNase I. This interesting method provided a novel solution to the challenge of linking RNA strands with hydrophobic molecules, and the outcome has improved the efficacy of RNA therapeutics [ 88 ]. To further increase therapeutic efficiency, another study has also reported that the co-delivery of small-molecule anticancer drugs and nucleotide molecules simultaneously could show a synergistic effect for specific tumor treatment [ 89 ].…”
Section: Bioanalytical and Biomedical Applications Of Dna–lipid Probesmentioning
confidence: 99%